Panama : Request for Purchase under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Panama. (IMF Staff Country Reports; Country Report ;, 2020)
This paper focuses on Panama's Request for Purchase Under the Rapid Financing Instrument. The coronavirus disease 2019 pandemic has disrupted Panama's economy and created urgent balance of payments (BOP) and fiscal financing needs. The government has resolutely implemented measures to contain and mitigate the spread of the pandemic. However, significant uncertainties remain, and the economic fallout could intensify further if containment measures must be extended. The authorities stand ready to continue cooperating with the IMF in finding solutions to the balance of payments and fiscal imbalances. Measures have also been taken to maintain financial sector stability, including by allowing banks to use the accumulated dynamic provisioning to improve their liquidity position and absorb the impact of potential credit losses. The IMF emergency support under the Rapid Financing Instrument will help provide much needed resources to address BOP needs and support essential pandemic-related health expenditure. The support of other international financial institutions and development partners is crucial to close the remaining BOP and budgetary gaps, ease the adjustment burden, and preserve economic growth.